2012
DOI: 10.1007/s11012-012-9582-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of relationships between residual magnetic field and residual stress

Abstract: The impact of stress on changes in magnetisation is one of the most complex issues of magnetism. Magnetic methods make use of the impact of stress on permeability, hysteresis and magnetic Barkhausen noise, which are examined with fields with a high strength and a small frequency. The paper presents an analysis of the impact of residual stress resulting from inhomogeneous plastic deformations in the notch area of the examined samples on the changes in the strength of the residual magnetic field (RMF). The RMF o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Several authors propose the in-plane (often referred to as tangential) field component to be suitable for qualitative and quantitative assessments of a component’s stress state [ 13 , 28 , 31 , 32 , 33 ]. Thus, if the magnetic field strengths correlated with stresses, then the disregard of topography and variable sensors to surface distances could, especially for pronounced surface reliefs, lead to an underestimation of the actual stress state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors propose the in-plane (often referred to as tangential) field component to be suitable for qualitative and quantitative assessments of a component’s stress state [ 13 , 28 , 31 , 32 , 33 ]. Thus, if the magnetic field strengths correlated with stresses, then the disregard of topography and variable sensors to surface distances could, especially for pronounced surface reliefs, lead to an underestimation of the actual stress state.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the directionality of magnetic (vector) components and mechanical tensors (and their components) is also hardly considered. For example, some authors propose considering the magnetic field components acting parallel to the surface (hereafter referred to as in-plane components H x and H y ) for correlations with the stress state, e.g., in [ 13 , 28 , 31 , 32 , 33 ], while others suggest analyzing the normal field component perpendicular to the surface, e.g., in [ 16 , 19 , 34 ] (hereafter referred to as H z ). Moreover, inhomogeneous plastic deformation (e.g., during necking in tensile testing) causes surface topographies, whose significance has so far not been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the interest of scientific community in the study of magneto-mechanical effects for diagnostics purposes is clearly noticeable [7,18,[23][24][25][26][27]. Historically, most probably the first attempt to avail of magnetic methods in order to determine residual stress in cylindrical metal bars was undertaken in 1971 by Abuku and Cullity, who have carried out a number of measurements of the reversible effective permeability at different bias field strengths for nickel and steel rods and concluded that this quantity increases almost linearly with tensile stress [28].…”
Section: Discussionmentioning
confidence: 99%
“…Metal magnetic memory (MMM) is a relatively novel method introduced by Anatoly A. Dubov [1][2][3], that proved its effectiveness in detecting the micro-damage in ferro-magnets due to the stress concentration [4,[8][9][10]. The basic principle of MMM method is the self-magnetic flux leakage (SMFL) signal that correlates with the degree of stress concentration [6][7][8]. This method allows detecting early damage of ferromagnetic material through performing measurement in the earth magnetic field, without the use of a special magnetizing device.…”
Section: Introductionmentioning
confidence: 99%